Design and Structural Analysis of Fighter Aircraft’s Bomb Release Mechanism subjected to Aerodynamic and Inertial Loads using FEA - Swarnakari, Sindura; G., Raja Singh Thangadurai (International Journal of Engineering and Technology, 2020)
This work speaks about the advancement of the design of a bomb rack unit’s component, to carry out the ideal execution for the ejection of the bomb from a supporting body where the suspension, separation, and ejection of the store are decidedly organized and controlled. Initially, the aircraft bomb rack unit (BRU) was examined hypothetically. The structure of the bomb rack unit is designed considering the military standards. Nitty-gritty investigation was performed for the critical case, capacity and reaction of the BRU among the stacking blends using the Finite Element Method for Static and dynamic conditions and corresponding results were illustrated.